2019
DOI: 10.1063/1.5064366
|View full text |Cite
|
Sign up to set email alerts
|

Field emission energy distribution and three-terminal current-voltage characteristics from planar graphene edges

Abstract: We demonstrate field emission from an integrated three-terminal device using a suspended planar graphene edge as the source of vacuum electrons. Energy spectra of the emitted electrons confirm the field-emission mechanism. The energy spectra produced by graphene grown by chemical vapor deposition and reduced graphene oxide are compared. The drain-source voltage required to produce a given drain current increases when negative voltages are applied to the gate, confirming field-effect transistor operation. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1
19

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 34 publications
0
10
1
19
Order By: Relevance
“…The tempera- ture reduction was estimated [40] to be only about 60 to 70 K due to poor thermal conductivity of our setup. Our spectra are ∼2-3 time narrower than a metallic emission peak, ∼15 time narrower than previous measurements on graphene [13], six times narrower than one of the theoretical value [19] and 3 time larger than the other [20], which is surprisingly narrow at ∼0.06 eV, to our knowledge only once achieved for FE in any experiment [43]. A final point is that our individual peaks all have the asymmetric form characteristic of tunneling from a metal through a triangular barrier which is not the case of the theoretical prediction whose peaks do not appear to have a high energy temperature edge.…”
Section: Fig 8 Fowler-nordheim Curves On Pristine Graphene (Top) Acontrasting
confidence: 66%
See 3 more Smart Citations
“…The tempera- ture reduction was estimated [40] to be only about 60 to 70 K due to poor thermal conductivity of our setup. Our spectra are ∼2-3 time narrower than a metallic emission peak, ∼15 time narrower than previous measurements on graphene [13], six times narrower than one of the theoretical value [19] and 3 time larger than the other [20], which is surprisingly narrow at ∼0.06 eV, to our knowledge only once achieved for FE in any experiment [43]. A final point is that our individual peaks all have the asymmetric form characteristic of tunneling from a metal through a triangular barrier which is not the case of the theoretical prediction whose peaks do not appear to have a high energy temperature edge.…”
Section: Fig 8 Fowler-nordheim Curves On Pristine Graphene (Top) Acontrasting
confidence: 66%
“…In Ref. [13] peak widths of ∼2 eV were shown that shifted to lower energy with increasing applied field. On the theoretical side there is an increasing body of work on FE from graphene edges [19][20][21][22][23][24][25] and reference therein of which two predict the energy distribution [19,20].…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…1.6 Κατανομή ενέργειας εκπομπής πεδίου και χαρακτηριστικές ρεύματος-τάσης από επίπεδες ακμές γραφενίου Η εκπομπή πεδίου από τις ακμές του γραφενίου που κατασκευάζονται σε επίπεδα υποστρώματα μπορούν να χρησιμοποιηθούν ως πηγές ηλεκτρονίων για ηλεκτρονικές συσκευές κενού, με τη μεταφορά να γίνεται παράλληλα με την επιφάνεια του υποστρώματος. Αυτή η ομοιόμορφη αρχιτεκτονική που αναπτύχθηκε από την ομάδα των Jonathan L. Shaw , John B. Boos, Byoung Don Kong, Jeremy T. Robinson και Glenn G. Jernigan, όπου όλα τα ηλεκτρόδια είναι διαμορφωμένα σε ένα κοινό επίπεδο υπόστρωμα χρησιμοποιώντας απλή λιθογραφία, επιτρέπει την εύκολη ενσωμάτωση και επεκτασιμότητα παρόμοια με τις συσκευές στερεάς κατάστασης [11]. Το γραφένιο έχει εξαιρετικά υψηλή θερμική αγωγιμότητα, μηχανική αντοχή και χημική σταθερότητα, οι οποίες αποτελούν βασικές απαιτήσεις για μια επιτυχημένη πηγή εκπομπής πεδίου.…”
Section: το τρανζίστορ κενού από το Nasa Ames Research Centerunclassified